Reconstruction of law criminal development on victims of restoration as form of renewal Criminal law - Muhammad Salam Amrullah (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
The crime of rape carried out by people, experiencing a development in criminal law, the formulation of offenses in the Criminal Code makes the criminal act, does not give a sense of justice to victims where the threat of punishment is relatively small and there are multiple interpretations of legal norms, while victims suffer a psychological loss which makes the victim lose his identity. In addition, the scope of the multi-interpretive criminal reparations is due to the unclear norms which regulate, for example, the category of rape itself. This research is a normative legal research that examines relevant laws and regulations and conceptualizes the law as the norm. From the results of the study found the unclear norms stipulated in article 285 of the Criminal Code, which resulted in the application of law enforcement to victims resulting in legal uncertainty, an increasingly broad category of actions while the legal norms did not specify the actions of the rape, from the results of the research the revision of the Criminal Code as a form of renewal of criminal law specifically article 285..